2015
DOI: 10.1155/2015/846045
|View full text |Cite
|
Sign up to set email alerts
|

New and Emerging Strategies in Platelet-Rich Plasma Application in Musculoskeletal Regenerative Procedures: General Overview on Still Open Questions and Outlook

Abstract: Despite its pervasive use, the clinical efficacy of platelet-rich plasma (PRP) therapy and the different mechanisms of action have yet to be established. This overview of the literature is focused on the role of PRP in bone, tendon, cartilage, and ligament tissue regeneration considering basic science literature deriving from in vitro and in vivo studies. Although this work provides evidence that numerous preclinical studies published within the last 10 years showed promising results concerning the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 162 publications
(129 reference statements)
2
48
0
1
Order By: Relevance
“…However, these effects were dependent on the PRP composition [10]. Somehow data become controversial when in vivo settings are compared, since opposite outcomes are equally available in the scientific literature in favor [11][12][13][14][15][16][17][18][19][20][21] or against [19,[22][23][24][25][26][27] the addition of PRP to biologic and synthetic graft materials for bone regeneration purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However, these effects were dependent on the PRP composition [10]. Somehow data become controversial when in vivo settings are compared, since opposite outcomes are equally available in the scientific literature in favor [11][12][13][14][15][16][17][18][19][20][21] or against [19,[22][23][24][25][26][27] the addition of PRP to biologic and synthetic graft materials for bone regeneration purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in 2001, 1 PRF has been extensively used in dentistry for a variety of procedures, and its effectiveness has been demonstrated for extraction socket management, 8 gingival recessions, 9–11 intrabony defect regeneration, 12 , 13 and sinus elevation procedures 7 . Major advantages include having completely immune‐compatible growth factors collected at relatively no costs without anticoagulants 14–17 . While initial and early experiments revealed PRP contained high concentrations of autologous growth factors (up to 6 to 8 times higher than normal blood concentrations), including platelet‐derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and transforming growth factor (TGF)‐ÎČ1, 18 PRF has since been shown to release even higher total growth factors over a more extended period of time 19 …”
mentioning
confidence: 99%
“…Histopathological examination showed that CBHA could induce new bone formation as a bone substitute in rabbit tibial bone defect. PRP, an inexpensive source rich in growth factors has emerged as an adjuvant therapy that may accelerate regenerative process recently [24][25][26][27] . Numerous experimental studies have applied PRP in association with bone grafts and substitutes; only some were successful [24,27,35] .…”
Section: Discussionmentioning
confidence: 99%
“…Another biologic source that has widely introduced lately is platelet rich plasma (PRP); defined as a fraction of blood which platelet concentration is above baseline in it. PRP have been applied as an economical angiogenic orthobiologic in association with ceramics such as hydroxyapatite and majority of studies reported promising results; however some found opposite outcome so its regenerative capability is still controversial [24][25][26][27] . The aim of present study was to evaluate in-vivo effectiveness of raw CB and CBHA prepared by hydrothermal synthesis along with PRP in bone repair and to investigate probable synergism between these biomaterials.…”
Section: Introductionmentioning
confidence: 99%